2001
DOI: 10.1046/j.1365-2591.2001.00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Periradicular surgery of molars: a prospective clinical study with a one‐year follow‐up

Abstract: The outcome of the present study and data of recently published studies show that periradicular surgery may result in a predictable treatment outcome in molars with persistent periradicular lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
3
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 35 publications
0
28
3
1
Order By: Relevance
“…The toxicity of Super EBA is in agreement with some studies (29,30) but in disagreement with others (3). Regarding the clinical performance of Super EBA, high success rates have been reported (31). The HPLC analysis showed that zinc oxide-eugenol cements released both eugenol and zinc in considerable amounts.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of Super EBA is in agreement with some studies (29,30) but in disagreement with others (3). Regarding the clinical performance of Super EBA, high success rates have been reported (31). The HPLC analysis showed that zinc oxide-eugenol cements released both eugenol and zinc in considerable amounts.…”
Section: Discussionmentioning
confidence: 99%
“…These developments have not only permitted greatly improved postoperative course of healing, but they have also documented improved long-term results. The reported radiographic success rates of studies with modern microscopic surgical endodontic procedures often exceed 90% (102)(103)(104). Survival rates can be extrapolated to be even higher than the reported success rates.…”
Section: If Apical Periodontitis Persists or Develops After Root Canamentioning
confidence: 97%
“…Periradicular surgery is indicated in cases of unsuccessful outcomes after primary root canal therapy followed by nonsurgical retreatment. The goal of periradicular surgery is the removal of diseased periapical tissues and the sealing of the apical root canal system to facilitate the regeneration of hard and soft tissues, including the formation of new attachment cells (11).…”
mentioning
confidence: 99%